Black women on the move: individual and collective creations for lives with dignity and rights (Práxis Educativa, 2022)
This article contains three axes: the determination for a dignified life; 33 years of national and international organization; and creativity in the service of the academic construction of knowledge. Such an organization is historic, and, in the search for broadening the feminist, anti-racist and anti-homophobic platform, black women made numerous criticisms regarding the invisibility of their political action in social movements (especially the black and feminist ones) and in society. The most direct challenge refers to the secondary way of treating their oppression and organization. Thus, whether through political discourses, behaviors and/or theoretical production, black women have historically appeared as implicit subjects. Up to date, motivated by the search to overcome racism, sexism, LGBTphobia and social, economic and social inequalities, black women have been successful in their organizational process with political, social and academic activism.Keywords: Black women on the move. Organization of black women. Racism, sexism and LGBTphobia.